A coated modified lithium iron phosphate electrode material and a manufacturing method thereof
By introducing polypyrrole nanotube-nitrogen doped carbon composite coated structure into the lithium iron phosphate electrode material, the problems of low conductivity and poor rate performance of lithium iron phosphate electrode material are solved, and better electrochemical performance is achieved.
Patent Information
- Application Number
- CN202411016304.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-27
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-07-27
AI Technical Summary
The low conductivity and poor rate performance of lithium iron phosphate electrode materials limit their application in lithium-ion batteries.
By combining the polypyrrole nanotube crosslinked modified body with lithium iron phosphate, a multi-layer structure is formed, and a polypyrrole nanotube-nitrogen doped carbon composite coated modified lithium iron phosphate electrode material is formed through hydrothermal reaction and high-temperature calcination.
The electrochemical performance of lithium iron phosphate electrode material is improved, its conductivity and cyclic stability are enhanced, and the rate performance is improved.
Smart Images

Figure CN118954461B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrode materials, and in particular to a coated modified lithium iron phosphate electrode material and a manufacturing method thereof. Background Art
[0002] In the era of rapid development of science and technology, energy and environment have gradually become important topics. With the increasing depletion of fossil energy and environmental degradation, the concept of environmental protection has gradually become popular. Therefore, using clean energy to replace fossil energy has become a top priority. Among various clean energy sources, electric energy is at the core. In order to achieve large-scale application of electric energy, energy storage devices are required. Batteries are one of the most common energy storage devices. Among various batteries, lithium-ion batteries have become one of the most widely used energy storage devices due to their high energy density and environmental friendliness.
[0003] Among the various components of lithium-ion batteries, the quality of the positive electrode material will directly have a decisive impact on the comprehensive performance of lithium-ion batteries. The current positive electrode material system is mainly concentrated in lithium-containing transition metal oxides, such as lithium manganese oxide, lithium nickel oxide, lithium iron phosphate, etc., but lithium manganese oxide and lithium nickel oxide are relatively difficult to synthesize and have low commercial appeal. Lithium iron phosphate has a higher theoretical specific capacity, good stability, and is environmentally friendly, so its current commercial application rate is relatively high. However, lithium iron phosphate itself is a semiconductor material, so it has disadvantages such as low conductivity and poor rate performance, which has gradually restricted the application of lithium iron phosphate in lithium-ion batteries.
[0004] In order to solve the above problems, the invention patent with publication number CN114927655B discloses a multi-layer coated lithium iron phosphate electrode material and its preparation method and application. By forming a multi-layer carbon-coated structure of lithium iron phosphate electrode material, the lithium iron phosphate electrode material can have excellent electrochemical properties. Therefore, the performance of the lithium iron phosphate electrode material can be improved by surface coating. Summary of the invention
[0005] In order to solve the problems mentioned in the background technology, the object of the present invention is to provide a coated modified lithium iron phosphate electrode material and a method for manufacturing the same.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A method for manufacturing a coated modified lithium iron phosphate electrode material comprises the following steps:
[0008] The first step is to mix the cross-linked modified polypyrrole nanotubes with purified water, and ultrasonically disperse them for 20-30 minutes to form a mixed solution, and then add ferrous sulfate, phosphoric acid and ascorbic acid to the mixed solution, and stir and mix to form a precursor solution;
[0009] The second step is to dissolve lithium hydroxide in purified water to prepare a lithium hydroxide aqueous solution;
[0010] Step 3: slowly add the lithium hydroxide aqueous solution to the precursor solution under continuous stirring, and after the addition, ultrasonically treat it at an ultrasonic frequency of 80-100kHz for 20-40min, then pour it into a reaction kettle, increase the temperature to carry out a hydrothermal reaction, and after the reaction is completed, cool it down, discharge it, and undergo washing and vacuum drying to form an electrode material precursor;
[0011] The fourth step is to place the electrode material precursor in a tubular furnace, pass nitrogen protection, and perform calcination. After the calcination, the coated modified lithium iron phosphate electrode material can be obtained.
[0012] Specifically, the cross-linked polypyrrole nanotube modifier is firstly ultrasonically mixed with ferrous sulfate, phosphoric acid and ascorbic acid to form a precursor solution, and then the precursor solution is mixed with a lithium hydroxide aqueous solution, and after ultrasonic mixing, a hydrothermal reaction is carried out. During the hydrothermal reaction, the lithium iron phosphate crystal nucleus will break through the port potential barrier of the tube diameter and pores of the cross-linked polypyrrole nanotube modifier during the liquid phase flow generated by high temperature and high pressure, enter the pores in the tube core of the cross-linked polypyrrole nanotube modifier, and grow in situ to form a cross-linked polypyrrole nanotube modifier coated with lithium iron phosphate, that is, an electrode material precursor, and then the cross-linked polypyrrole nanotube modifier is calcined into carbon by high-temperature calcination, and finally a polypyrrole nanotube-nitrogen-doped carbon composite coated modified lithium iron phosphate electrode material is formed.
[0013] As a further solution of the present invention, in the first step, the preparation method of the cross-linked modified polypyrrole nanotube is as follows:
[0014] Step S1, adding ferric chloride to a methyl orange solution, stirring at room temperature for 10-15 minutes to form a homogeneous solution, then adding pyrrole monomer to the homogeneous solution, and after the addition, continuing to react at room temperature for 6-12 hours, discharging, washing and vacuum drying to obtain polypyrrole nanotubes;
[0015] Step S2, dispersing polypyrrole nanotubes in N,N-dimethylformamide, mechanically stirring, then adding an alkaline catalyst and stirring, after mixing, continuing to add an agarose crosslinking agent, after the addition is completed, controlling the temperature to 50-60° C., keeping the temperature and stirring for 6-9 hours, cooling the material, pouring it into a mold and letting it stand to form a gel, then transferring it to a freeze dryer, keeping it at a temperature of -50° C. for 12-18 hours, taking it out, grinding and crushing it, and obtaining a crosslinked modified polypyrrole nanotube.
[0016] As a further embodiment of the present invention, in step S2, the mass ratio of the polypyrrole nanotubes to the agarose crosslinking agent is 1:6-8.
[0017] As a further embodiment of the present invention, in step S2, the alkaline catalyst is potassium hydroxide or sodium hydroxide.
[0018] Specifically, ferric chloride is first used as a catalyst to catalyze the in-situ polymerization of pyrrole monomers in a methyl orange solution system to obtain polypyrrole nanotubes. Then, under the action of an alkaline catalyst, the secondary amine groups in the polypyrrole nanotube structure are replaced and cross-linked with the halogen substituents in the agarose cross-linker structure. Since agarose has gel properties, it will form a colloid after standing. After freeze-drying, a cross-linked modified polypyrrole nanotube with an aerogel morphology can be formed.
[0019] As a further embodiment of the present invention, in step S2, the preparation method of the agarose cross-linking agent is as follows:
[0020] Agarose and dimethyl sulfoxide are mixed and stirred to form a uniform mixture, and then 2-chloroethyl isocyanate is added to the mixture, and a tin metal catalyst is added at the same time. After the addition, the temperature is gradually increased to 60-70°C, and stirring is maintained for 2-4 hours under this temperature condition, and then the temperature is reduced and the product is collected by filtration to obtain an agarose cross-linking agent. The whole process is carried out under nitrogen protection.
[0021] As a further embodiment of the present invention, the tin metal catalyst is at least one of dibutyltin dilaurate, stannous octoate, dibutyltin diacetate or dibutyltin didodecylsulfide.
[0022] Specifically, the agarose structure contains active substituted hydroxyl groups, which can undergo an amine esterification reaction with the isocyanate groups in the 2-chloroethyl isocyanate structure under the action of a tin metal catalyst to form an agarose derivative containing a large number of halogen substituents in the structure, namely, an agarose cross-linker.
[0023] As a further embodiment of the present invention, in the third step, the molar ratio of ferrous sulfate, phosphoric acid and lithium hydroxide in the reaction solution is 3:1:1.
[0024] As a further solution of the present invention, in the third step, the temperature of the hydrothermal reaction is 160-180° C. and the time is 6-8 hours.
[0025] As a further solution of the present invention, in the fourth step, the calcination temperature is 700-800° C. and the calcination time is 1-3 hours.
[0026] A coated modified lithium iron phosphate electrode material is prepared by adopting the above-mentioned manufacturing method.
[0027] Beneficial effects of the present invention:
[0028] (1) The electrode material prepared by the present invention is a polypyrrole nanotube-nitrogen-doped carbon composite material coated with lithium iron phosphate. Since the lithium iron phosphate is in-situ grown in the polypyrrole nanotube cross-linked modified body, the particle size of the lithium iron phosphate can be effectively controlled. The lithium iron phosphate with a smaller particle size can show a larger specific surface area, which is conducive to accelerating the diffusion of lithium ions during the charge and discharge process, thereby improving the electrochemical performance of the battery. In addition, this coating structure can also help improve the structural stability of the lithium iron phosphate, so that the electrode material exhibits more excellent cycle stability.
[0029] (2) Since the cross-linked modified polypyrrole nanotubes have an aerogel morphology, during the hydrothermal process, lithium iron phosphate will not only grow in situ inside the polypyrrole nanotubes, but also in the pores of the aerogel. After high-temperature carbonization, agarose will be carbonized into nitrogen-doped porous carbon. The polypyrrole nanotubes exist in the nitrogen-doped porous carbon in the form of a skeleton, and the lithium iron phosphate will be evenly coated in the pores and tubes, avoiding the problem of agglomeration of small-sized lithium iron phosphate particles. In addition, the nitrogen-doped porous carbon has good electrical conductivity. Combined with the skeleton support of the polypyrrole nanotubes, the electrode material can exhibit excellent electrical conductivity, thereby solving the problem of poor battery rate performance caused by the poor electrical conductivity of the lithium iron phosphate electrode material.
[0030] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0032] Figure 1 This is a scanning electron microscope image of the cross-linked modified polypyrrole nanotube in Example 2 of the present invention. DETAILED DESCRIPTION
[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Example 1
[0035] Preparation of agarose crosslinker:
[0036] 2.4 g of agarose was mixed with dimethyl sulfoxide and stirred to form a uniform mixture. Then, 0.5 g of 2-chloroethyl isocyanate was added to the mixture and 0.1 g of dibutyltin dilaurate was added. After the addition, the temperature was gradually increased to 65° C. and stirred for 3 h under this temperature condition. Then, the temperature was lowered and the product was collected by filtration to obtain an agarose crosslinker. The whole process was carried out under nitrogen protection.
[0037] The organic element analysis of the agarose crosslinker was performed using a Vario EL IIICHN organic element analyzer. 0.2 g of the sample was taken as a test sample. The analysis showed that the percentage of carbon was 44.92% and the percentage of nitrogen was 4.15%. Since the agarose structure does not contain nitrogen, it is speculated that the nitrogen comes from the amine ester group produced by the amine esterification reaction of agarose and 2-chloroethyl isocyanate.
[0038] Example 2
[0039] Preparation of cross-linked modified polypyrrole nanotubes:
[0040] Step S1, adding 0.3 g of ferric chloride to 200 mL of methyl orange solution with a concentration of 4 mmol / L, stirring at room temperature for 15 min to form a homogeneous solution, then adding 1.2 g of pyrrole monomer to the homogeneous solution, and after the addition, continuing to react at room temperature for 9 h, discharging, washing and vacuum drying to obtain polypyrrole nanotubes;
[0041] Step S2, dispersing 1.5 g of polypyrrole nanotubes in N,N-dimethylformamide, mechanically stirring, then adding 0.3 g of potassium hydroxide and stirring, after mixing, continuing to add 10 g of agarose crosslinking agent, after the addition is completed, controlling the temperature to 60° C., keeping warm and stirring for 8 hours, cooling and discharging, pouring into a mold and standing to form a gel, then transferring to a freeze dryer, keeping it at -50° C. for 18 hours, taking it out, grinding and crushing, and obtaining a cross-linked modified polypyrrole nanotube.
[0042] Figure 1 : is a scanning electron microscope image of the cross-linked modified polypyrrole nanotube. It can be observed that the cross-linked modified polypyrrole nanotube presents a morphology of interwoven polypyrrole nanotubes and has a rich pore structure, which is conducive to the entry of lithium iron phosphate crystal nuclei and in-situ growth.
[0043] Example 3
[0044] A method for manufacturing a coated modified lithium iron phosphate electrode material comprises the following steps:
[0045] The first step is to mix 1.2 g of the cross-linked modified polypyrrole nanotube with 50 mL of purified water, and ultrasonically disperse for 30 min to form a mixed solution. Then, 0.1 g of ferrous sulfate, 0.02 g of phosphoric acid and 0.01 g of ascorbic acid are added to the mixed solution, and the mixture is stirred to form a precursor solution.
[0046] Step 2: Dissolve 0.005 g of lithium hydroxide in 50 mL of purified water to prepare a lithium hydroxide aqueous solution;
[0047] Step 3: slowly add the lithium hydroxide aqueous solution obtained in the second step to the precursor solution obtained in the first step under continuous stirring. After the addition, ultrasonic treatment is performed at an ultrasonic frequency of 100 kHz for 30 minutes to form a reaction solution, which is then poured into a reaction kettle and the temperature is increased to 170° C. to perform hydrothermal reaction for 8 hours. After the reaction is completed, the temperature is lowered and the material is discharged. After washing and vacuum drying, an electrode material precursor is formed.
[0048] The fourth step is to place the electrode material precursor in a tubular furnace, pass nitrogen protection, and roast at 750°C for 2 hours. After the roasting, the coated modified lithium iron phosphate electrode material can be obtained.
[0049] Comparative Example 1
[0050] A method for manufacturing a lithium iron phosphate electrode material comprises the following steps:
[0051] Step 1: Add 0.1 g of ferrous sulfate, 0.02 g of phosphoric acid and 0.01 g of ascorbic acid to 50 mL of purified water and stir to form a precursor solution.
[0052] Step 2: Dissolve 0.005 g of lithium hydroxide in 50 mL of purified water to prepare a lithium hydroxide aqueous solution;
[0053] Step 3: slowly add the lithium hydroxide aqueous solution obtained in the second step to the precursor solution obtained in the first step under continuous stirring. After the addition, ultrasonic treatment is performed at an ultrasonic frequency of 100 kHz for 30 minutes to form a reaction solution, which is then poured into a reaction kettle and the temperature is increased to 170° C. to perform hydrothermal reaction for 8 hours. After the reaction is completed, the temperature is lowered and the material is discharged. After washing and vacuum drying, an electrode material precursor is formed.
[0054] The fourth step is to place the electrode material precursor in a tubular furnace, pass nitrogen protection, and roast at 750°C for 2 hours. After the roasting, the coated modified lithium iron phosphate electrode material can be obtained.
[0055] Test Case
[0056] According to the mass ratio of 75:15:10, the electrode materials, acetylene black and polyvinylidene fluoride binder in Example 3 and Comparative Example 1 were weighed and mixed, and then N-methylpyrrolidone was added for stirring. After a uniform viscous slurry was formed, it was coated on the surface of an aluminum foil with a diameter of 15 mm, and then dried at a temperature of 60°C and pressed into a pole piece, which was used as the positive pole piece. In an argon atmosphere protective glove box, the positive electrode shell, the positive electrode sheet, the diaphragm, the elemental lithium negative electrode sheet, the foamed nickel, and the negative electrode shell were stacked in order from bottom to top, and the electrolyte LB-301 was injected to assemble into a button battery, which was then sealed with a sealing machine and electrochemical performance tested. The results are recorded in the following table:
[0057] Table 1 - Cycle performance test results
[0058] Current density (A / g) Specific capacity (mAh / g) Retention rate after 100 cycles (%) Example 3 0.1 198.4 94.5 Comparative Example 1 0.1 169.1 89.8
[0059] Analysis of the test data in Table 1 shows that at a current density of 0.1 A / g, the electrode material prepared in Example 3 of the present invention can exhibit a higher specific capacity and better cycle stability. This is because after coating, the polypyrrole nanotubes and carbon materials can provide additional electrochemically active sites and can limit the volume change of lithium iron phosphate, while the electrode material in Comparative Example 1 is not coated, and obviously has poor specific capacity and cycle stability.
[0060] Table 2 - Rate performance test results
[0061]
[0062] Analysis shows that when the current density changes, the electrode material in Example 3 has a lower specific capacity reduction rate and exhibits better rate performance. This is because the conductivity of lithium iron phosphate is effectively improved after coating, while the uncoated lithium iron phosphate has poor conductivity, so the rate performance is obviously poor.
[0063] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.
Claims
1. A method for manufacturing a coated modified lithium iron phosphate electrode material, characterized in that: The following steps are involved: The first step is to mix the cross-linked modified polypyrrole nanotubes with purified water, and ultrasonically disperse them for 20-30 minutes to form a mixed solution, and then add ferrous sulfate, phosphoric acid and ascorbic acid to the mixed solution, and stir and mix to form a precursor solution; The second step is to dissolve lithium hydroxide in purified water to prepare a lithium hydroxide aqueous solution; Step 3: slowly add the lithium hydroxide aqueous solution to the precursor solution under continuous stirring, and after the addition, ultrasonically treat it at an ultrasonic frequency of 80-100kHz for 20-40min to form a reaction solution, which is then poured into a reaction kettle and heated to perform a hydrothermal reaction. After the reaction is completed, the temperature is lowered and the material is discharged, and after washing and vacuum drying, an electrode material precursor is formed; Step 4: Place the electrode material precursor in a tubular furnace, pass nitrogen protection, and calcine. After calcination, the coated modified lithium iron phosphate electrode material can be obtained; The preparation method of the cross-linked modified polypyrrole nanotube is as follows: Step S1, using methyl orange solution as a reaction medium and ferric chloride as a catalyst to catalyze polymerization of pyrrole monomers to prepare polypyrrole nanotubes; Step S2, dispersing polypyrrole nanotubes in N,N-dimethylformamide, mechanically stirring, then adding an alkaline catalyst and stirring, after mixing, continuing to add an agarose crosslinking agent, after the addition is completed, controlling the temperature to 50-60° C., keeping the temperature and stirring for 6-9 hours, cooling the material, pouring it into a mold and letting it stand to form a gel, then transferring it to a freeze dryer, keeping it at a temperature of -50° C. for 12-18 hours, taking it out, grinding and crushing it, and obtaining a crosslinked modified polypyrrole nanotube.
2. The method for manufacturing a coated modified lithium iron phosphate electrode material according to claim 1, characterized in that: In step S2, the mass ratio of the polypyrrole nanotubes to the agarose crosslinking agent is 1:6-8.
3. The method for manufacturing a coated modified lithium iron phosphate electrode material according to claim 1, characterized in that: In step S2, the alkaline catalyst is potassium hydroxide or sodium hydroxide.
4. The method for manufacturing a coated modified lithium iron phosphate electrode material according to claim 1, characterized in that: In step S2, the preparation method of the agarose cross-linking agent is as follows: Agarose and dimethyl sulfoxide are mixed and stirred to form a uniform mixture, and then 2-chloroethyl isocyanate is added to the mixture, and a tin metal catalyst is added at the same time. After the addition, the temperature is gradually increased to 60-70°C, and stirring is maintained for 2-4 hours under this temperature condition, and then the temperature is reduced and the product is collected by filtration to obtain an agarose cross-linking agent. The whole process is carried out under nitrogen protection.
5. The method for manufacturing a coated modified lithium iron phosphate electrode material according to claim 4, characterized in that: The tin metal catalyst is at least one of dibutyltin dilaurate, stannous octoate, dibutyltin diacetate or dibutyltin didodecylsulfide.
6. The method for manufacturing a coated modified lithium iron phosphate electrode material according to claim 1, characterized in that: In the third step, in the reaction solution, the molar ratio of ferrous sulfate, phosphoric acid and lithium hydroxide is 3:1:
1.
7. The method for manufacturing a coated modified lithium iron phosphate electrode material according to claim 1, characterized in that: In the third step, the temperature of the hydrothermal reaction is 160-180° C. and the time is 6-8 hours.
8. The method for manufacturing a coated modified lithium iron phosphate electrode material according to claim 1, characterized in that: In the fourth step, the calcination temperature is 700-800° C. and the calcination time is 1-3 hours.
9. A coated modified lithium iron phosphate electrode material, characterized in that: The method according to claim 1 is used to prepare the present invention.
Citation Information
Patent Citations
A multilayer coated lithium iron phosphate electrode material, its preparation method and application
CN114927655B
Method for preparing carbon nano tube coated lithium iron phosphate cathode material
CN102856549A
Preparation method of carbon gel-coated lithium iron phosphate positive electrode material
CN106207169A